Dual role for N-2-acetylornithine 5-aminotransferase from Pseudomonas aeruginosa in arginine biosynthesis and arginine catabolism. - Voellmy, R (1975)
In Pseudomonas aeruginosa N-2-acetylornithine 5-aminotransferase (ACOAT), the fourth enzyme of arginine biosynthesis is induced about 15-fold by cultivating the organism on a medium with L-arginine as the sole carbon and nitrogen source. Synthesis of the enzyme is subject to catabolite repression and nitrogen source. Synthesis of the enzyme is subject to catabolite repression by a variety of carbon sources. ACOAT from strain PAO 1 was purified over 40-fold to electrophoretic homogeneity. A molecular weight of approximately 110,000 was obtained by thin-layer gel filtration. Electrophoresis in sodium dodecyl sulfate gels gave a single band corresponding to a molecular weight of 55,000. Purified ACOAT catalyzes the transamination of N-2-acetyl-L-ornithine as well as of L-ornithine with 2-oxoglutarate (Km values of 1.1, 10.0, and 0.7 mM, respectively). With N-2-acetyl-L-ornithine as amino donor, the pH-optimum of the enzymatic reaction is 8.5; with L-ornithine as amino donor, 9.5. The catalytic properties of ACOAT as well as the regulation of its synthesis indicate that in P. aeruginosa this enzyme functions in the biosynthesis as well as in the catabolism of L-arginine.